The Influence of Muslim Batik Entrepreneurs' Financial Literacy of The Banking Sector on Productivity - Norida Canda Sakti; Martinus Legowo; Herrukmi Septa Rinawati; FX Sri Sadewo; Sugeng Harianto; Diyah Utami (Universitas Negeri Surabaya, 2021)
The batik business in the Islamic community of the North coast of East Java is categorized as a micro and small business. One of the main problems of the business is capital adequacy. Capital adequacy is one instrument to run and increase productivity. Although the government has provided soft capital loans through banking instruments and rural development program, not all micro and small businesses are willing and able to access it. It is heavily relied on the entrepreneurs' financial literacy on banking sector and their willingness to use banking access. The survey results show that there are variations of the financial literacy level of batik entrepreneurs on banking sector. Batik entrepreneur who have high financial literacy were motivated to access the bank financiang service and improve its productivity.Education and location play a significant role to financial literacy on banking sector.